2023
DOI: 10.1101/2023.03.20.533560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanograms of SARS-CoV-2 Spike Protein Delivered by Exosomes Induce Potent Neutralization of Both Delta and Omicron Variants

Abstract: Exosomes are emerging as potent and safe delivery carriers for use in vaccinology and therapeutics. A better vaccine for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is needed to provide improved, broader, longer lasting neutralization of SARS-CoV-2, a more robust T cell response, enable widespread global usage, and further enhance the safety profile of vaccines given the likelihood of repeated booster vaccinations. Here, we use Capricor's StealthXTM platform to engineer exosomes to express nat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Here we apply the STX technology to produce a multivalent protein-based exosome delivered vaccine, against both Influenza and SARS-CoV-2. Previously, we demonstrated that STX-S and STX-N can elicit robust humoral and cellular immune responses against different variants of SARS-CoV-2 viruses [5,6]. Similarly in the present study, monovalent STX-H3 vaccination induced both IgG and T-cell responses against H3.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Here we apply the STX technology to produce a multivalent protein-based exosome delivered vaccine, against both Influenza and SARS-CoV-2. Previously, we demonstrated that STX-S and STX-N can elicit robust humoral and cellular immune responses against different variants of SARS-CoV-2 viruses [5,6]. Similarly in the present study, monovalent STX-H3 vaccination induced both IgG and T-cell responses against H3.…”
Section: Discussionsupporting
confidence: 88%
“…Response was comparable to previous studies using single injection of either STX-H3 (Fig. 2) or STX-S [5,6] To characterize the T-cell response to the STX-H3-S cocktail vaccine, antigen-specific T-cell responses were measured by ELISpot (Fig. 3).…”
Section: Stx-h3+s Induces Strong Immunization Against H3 and Spike Pr...supporting
confidence: 79%
See 3 more Smart Citations